DESIGN AND IMPLEMENTATION OF VIRTUAL LOCAL AREA NETWORK NETWORK AT PT. EDS MANUFACTURING INDONESIA - Rustam Effendi; Yasin Efendi (Journal of Innovation And Future Technology (IFTECH), 2020)
The need for information and communication has become a fundamental thing in human life, marked by the increasing human activity that no longer sees the distance and time to communicate with and share information. In 1960, the US Department of Defense conducted research on computer networks. Research carried out is to build a computer network with a method that mimics the workings of the telephone network, where one computer can be connected to other computers, both in one location or area known as a Local Area Network (LAN), and even can be connected to a place or a different country known as a Wide Area Network (WAN). LAN limitations give birth to a VLAN technology that allows for the configuration of a virtualized computer network. The higher the level of demand and the increase in computer network users resulting in broadcasts and traffic on the network itself. The current condition of PT. EDS Manufacturing Indonesia does not yet have a computer network concept that is in line with company needs, computer network activities that occur every day require concepts that are appropriate to the company. Then it is necessary to design a VLAN concept that is expected to provide better results and make it easier for IP Address segmentation to manage broadcast and traffic on a computer network.